5(2x-4)-2(x+1)-17x=

Simple and best practice solution for 5(2x-4)-2(x+1)-17x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-4)-2(x+1)-17x= equation:


Simplifying
5(2x + -4) + -2(x + 1) + -17x = 0

Reorder the terms:
5(-4 + 2x) + -2(x + 1) + -17x = 0
(-4 * 5 + 2x * 5) + -2(x + 1) + -17x = 0
(-20 + 10x) + -2(x + 1) + -17x = 0

Reorder the terms:
-20 + 10x + -2(1 + x) + -17x = 0
-20 + 10x + (1 * -2 + x * -2) + -17x = 0
-20 + 10x + (-2 + -2x) + -17x = 0

Reorder the terms:
-20 + -2 + 10x + -2x + -17x = 0

Combine like terms: -20 + -2 = -22
-22 + 10x + -2x + -17x = 0

Combine like terms: 10x + -2x = 8x
-22 + 8x + -17x = 0

Combine like terms: 8x + -17x = -9x
-22 + -9x = 0

Solving
-22 + -9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + -9x = 0 + 22

Combine like terms: -22 + 22 = 0
0 + -9x = 0 + 22
-9x = 0 + 22

Combine like terms: 0 + 22 = 22
-9x = 22

Divide each side by '-9'.
x = -2.444444444

Simplifying
x = -2.444444444

See similar equations:

| -4(4u-1)+4u=9+3(2u-5) | | (-7x^2y)(-10x^3y^5)= | | 5b-20=15 | | 15q-14q=20 | | (-.75)(-8x)(1.3)(4y)(1)=c | | -3(d-7)+9=27 | | 2x^2+10-600=0 | | 2s+s=15 | | 3.6(x+9)+4.9x= | | -6=z/5-3 | | 14xy-35yz-63xz= | | 8c-4c=16 | | 2(3b-5)+6b=14 | | 1.6(x-5.5)=10.4 | | X(5+12)=52 | | x+3x+0=7x-15 | | -3y+8=14 | | 9(3x)=16 | | -2(a-2)+4=16 | | 8(3a-4)= | | -3n-8= | | 8x^4y+56x^2y^2-32x^2y= | | 1-9a=-15-2x | | -3(-5v+5)-v=4(v-2)-1 | | y=4/3x-2 | | 5/8y-8=8 | | -2(2p-1)-2(p-1)= | | -4(2X-3)+5X=33 | | 0.6x-13=2.2x-21 | | 4x-5=3(6+x)+6 | | 15+45-2x=15x+2x-5 | | 2x+37= |

Equations solver categories